A physiologically-based pharmacokinetic model of oseltamivir phosphate and its carboxylate metabolite for rats and humans - Guanghua Gao; Francis Law; Ricky Ngok Shun Wong; Nai Ki Mak; Mildred Sze Ming Yang (International Association of Physical Chemists (IAPC), 2019)
Oseltamivir phosphate (OP, Tamiflu®) is a widely used prodrug for the treatment of influenza viral infections. Orally administered OP is rapidly hydrolyzed by the carboxylesterases in animals to oseltamivir carboxylate (OC), a potent influenza virus neuraminidase inhibitor. The goals of this study were to develop and validate a physiologically-based pharmacokinetic (PBPK) model of OP/OC in rats and humans, and to predict the internal tissue doses for OP and OC in humans after receiving OP orally. To this end, a PBPK model of OP/OC was first developed in the rat, which was then scaled up to humans by replacing the physiological and biochemical parameters with human-specific values. The proposed PBPK model consisted of an OP and an OC sub-models each containing nine first-order, flow-limited tissue/organ compartments. OP metabolism to OC was assumed to carry out mainly by hepatic carboxylesterases although extra-hepatic metabolism also occurred especially in the plasma. The PBPK model was developed and validated by experimental data from our laboratories and from the literature. The proposed PBPK model accurately predicted the pharmacokinetic behavior of OP and OC in humans and rats after receiving a single or multiple doses of OP orally or an OC dose i.v. The PBPK model was used to predict the internal tissue doses of OP and OC in a hypothetical human after receiving the recommended dose of 75 mg/kg OP b.i.d. for 6 days. Steady-state OC concentrations in the plasma and major organs such as the lung and the brain were higher than the minimum in vitro IC50 reported for H1N1 influenza virus neuraminidase, confirming OP is an effective, anti-viral agent. OP side-effects in the gastrointestinal tract and brain of humans were explainable by the tissue doses found in these organs. The PBPK model provides a quantitative tool to evaluate the relationship between an externally applied dose of OP and the internal tissue doses in humans. As such the model can be used to adjust the dose regimens for adult patients in disease states e.g., renal failure and liver damage.